2018
DOI: 10.1136/sextrans-2018-053567
|View full text |Cite
|
Sign up to set email alerts
|

Dried blood spot and mini-tube blood sample collection kits for postal HIV testing services: a comparative review of successes in a real-world setting

Abstract: This comparative analysis suggests that in this community setting, the use of postal HIV DBS kits resulted in a significantly improved RRR compared with MT. The biggest factor was the large number of MT samples not analysed due to inadequate blood volumes. The unexpected level of false positive results in the MT samples needs confirming in larger studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 4 publications
0
32
1
Order By: Relevance
“…6 A comparative review between DBS and CBS HIV testing in the North-West England region showed that a large number of samples collected via the CBS method could not be processed due to insufficient sample being provided. 7 There is a lack of data evaluating the effectiveness of online testing for hepatitis B and syphilis.…”
Section: Introductionmentioning
confidence: 99%
“…6 A comparative review between DBS and CBS HIV testing in the North-West England region showed that a large number of samples collected via the CBS method could not be processed due to insufficient sample being provided. 7 There is a lack of data evaluating the effectiveness of online testing for hepatitis B and syphilis.…”
Section: Introductionmentioning
confidence: 99%
“…However, other studies have failed to demonstrate these benefits [16]. Considerable heterogeneity exists between the structural elements of these programs, including the type of rapid HIV test utilized (oral, dried blood spot, minitube) [11, 15, 16], the venue at which HIV/STI rapid self-testing is available for use (walk-in clinic, home) [13, 14], and test result delivery (electronically via secure website, provider phone call, text message) [11, 12, 15], which may explain the differences seen in program uptake. Although the CDC now supports the incorporation of HIV self-testing into large-scale testing programs [17], further investigation of the optimal utilization of the elements of self-testing programs is needed.…”
mentioning
confidence: 99%
“…A small UK study investigating HIV self-sampling in a service that switched from mini-tube (MT) to dried blood spot (DBS) samples demonstrated significantly better processing rates for DBS at 98.8% versus 55.7% for MT samples (P<0.001), driven primarily by inadequate MT blood volume. False-reactive rates were also higher for MT samples (5.4% vs. 0%) [47].…”
Section: Self-samplingmentioning
confidence: 89%